Can labour mobility reduce imbalances in the euro area? - Johannes Berger; Ludwig Strohner (EcoAustria - Institute for Economic Research, 2022)
Labour market developments in the Euro area diverged significantly since 2008. Economic literature frequently refers to labour mobility as pillar for the functioning of currency areas. Applying the CGE model PuMA, we quantitatively analyse to what extent labour mobility can contribute to reducing imbalances within the Euro area. Our results indicate that it can temporarily reduce unemployment and increase wages in periphery countries at the cost of somewhat higher unemployment in receiving countries. Overall, economic outcomes improve slightly. Although labour mobility has a positive effect on labour market imbalances, it cannot be seen as substitute for structural reforms.
Keywords: F22; D58; J11; J31; J61; J64; 330; international migration; wage level and structure; unemployment; general equilibrium models; Euro area